Behavioral Counseling Approach in Overcoming Student Delinquency Y (Case Study of MA Plus Nurul Islam Sekarbela Students) - Dedi Riyan Rizaldi Rizaldi (Widyadewata, 2023)
This study aims to find solutions in overcoming delinquent behavior in students through the implementation of behavioral counseling using positive reinforcement techniques. This type of research uses action research on counseling guidance (Action Research In Counseling). The subjects in this study were 2 students out of 31 students of class XI Religion MA Plus Nurul Islam who showed delinquent behavior. This method focuses on observation methods inside and outside the classroom. Data were analyzed by descriptive analysis which was carried out in 2 cycles/actions. The results showed that there was a decrease in delinquent behavior after counseling cycle 2 and the observations proved that the subject had shown many positive changes. This proves that the behavioral counseling approach is very effective in overcoming delinquent behavior in students.